Optically Transparent Flexible Broadband Metamaterial Absorber Based on Topology Optimization Design - Pingping Min (MDPI AG, 2021)
A conformal metamaterial absorber with simultaneous optical transparency and broadband absorption is proposed in this paper. The absorptance above 90% over a wide frequency range of 5.3–15 GHz can be achieved through topology optimization combined with a genetic algorithm (GA). The broadband absorption can be kept at incident angles within 45° and 70° for TE mode and TM mode, respectively. In the meantime, by employing transparent substrates, including polyvinyl chloride (PVC) and polyethylene terephthalate (PET), good optical transmittance and flexibility can be obtained simultaneously. The experimental results agree well with the numerical simulations, which further validates the reliability of our design and theoretical analysis. With its visible-wavelength transparency, flexibility, broadband absorption, low profile, excellent angle stability and polarization insensitivity, the proposed absorber is highly favored for practical applications in microwave engineering, such as electromagnetic interference and stealth technology. Moreover, the proposed design method of topology optimization can be extended to design the absorber quickly and efficiently, according to specific engineering requirements.